THE EFFECTS OF CALL (COMPUTER ASSISTED LANGUAGE LEARNING) TOWARD THE STUDENTS’ ENGLISH ACHIEVEMENT AND ATTITUDE - Asrifan, Andi; Zita, Cris T.; Vargheese, K. J.; T., Syamsu; Amir, Muhammad (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
The objectives of research this research was to find out whether or not the CALL affects the students’ achievement and to find out the students’ attitude in learning English by using CALL. This research applied quasi-experimental method was used in this research by using non-equivalent control class design. The researcher chose and placed the experimental and control design randomly. The researcher took the first-year students of SMK Negeri 1 Pancarijang Kabupaten Sidrap in academic year 2019-2020 as a research subject. Based on the data found in this research, the researcher concludes that; 1) The use of CALL affected the achievement of the first year students of SMK Negeri 1 Pancarijang Kabupaten Sidrap in academic 2012/2013. It was proved by the mean score of pretest and posttest which was obtained from experimental class was 52.44 and 74.59. While the mean scores of pretest and posttest for the control class were 48.03 and 56.48. After analyzing using SPSS 22.0, the researcher found that (0.00<0.05) where the p-value (0.00) at the level of significance (0.05) and the degree of freedom 66. It indicated that the alternative hypothesis (H1) was accepted and, of course, the null hypothesis (H0) was rejected. 2) The first-year students of SMK Negeri 1 Pancarijang Kabupaten Sidrap have a positive attitude in learning English through CALL. It was approved by the data that none of the student states negative statement to the use of CALL, 21 students (61.8%) was very favorable who get a score in interval 85-100 and 13 students (38.2%) were favorable in interval 69-84. From the data, the highest score of the students of the students is 100 which is categorized as very favorable, and the lowest score is 70 which is categorized favorable.